Canadian Geoscience Education Network:: A Grassroots Powerhouse - Vodden, Christy (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2009)
SUMMARY CGEN was founded in the early 1990s by the Canadian Geoscience Council, and now functions as the outreach arm of the Canadian Federation of Earth Sciences. The need to promote and publicize the earth sciences became clear in the 1980s with growing evidence of science illiteracy among the general public. CGEN, with its goal of raising public awareness of the earth sciences through improving the quality of earth science education and public outreach, has enjoyed explosive growth in the past few years, more than tripling its membership to roughly 300. CGEN membership now includes teachers, writers, artists, museum staff, and others, in addition to earth scientists. CGEN is the focal point for earth science education and outreach in Canada. Through it, people are connecting, developing new partnerships, learning from the successes of others, and sharing information, materials and ideas for teaching and promoting the earth sciences. CGEN supports six core programs, including Careers in Earth Science, EarthNet, EdGEO, Friends of Canadian Geoheritage, Geoscape Canada, and What on Earth.